2019
DOI: 10.3311/pptr.13759
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model Representation Framework for Cooperative Intelligent Transport Systems

Abstract: Cooperative Intelligent Transport Systems is C-ITS a set of ITS technologies that can provide services supported by the permanent, real time, information circulation among the components of the system. The paper aims to give an overview related to the modelling and evaluation possibilities of cooperative intelligent transportation system and to clarify the definition of the C-ITS and its differences from the regular ITS solutions. The paper introduce a proposed architecture of C-ITS modelling framework by desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…AVs will partially reduce or even eliminate human factors from traffic flow, reducing gap for lane changing, headway, reaction time using 360-degree sensors and cameras expected to increase road capacity, leading to lower congestion [3]. Communications and the exchange of information between AVs and the infrastructure, the Cooperative Intelligent Transportation System (C-ITS), is valuable to identify the traffic states on urban roads [4,5]. Moreover, it provides more information for intersection control, applying the best actions to improve traffic operations [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AVs will partially reduce or even eliminate human factors from traffic flow, reducing gap for lane changing, headway, reaction time using 360-degree sensors and cameras expected to increase road capacity, leading to lower congestion [3]. Communications and the exchange of information between AVs and the infrastructure, the Cooperative Intelligent Transportation System (C-ITS), is valuable to identify the traffic states on urban roads [4,5]. Moreover, it provides more information for intersection control, applying the best actions to improve traffic operations [6].…”
Section: Introductionmentioning
confidence: 99%
“…5 PCU equal to 37.87% of base scenario delay. Implementation of AVs with different factors has also increases mean network speed by 4.08%, reaching 45.20 km/h compared to43.43 …”
mentioning
confidence: 99%
“…The initial estimations on GHG emission reduction for AVs can be expected from a minimal impact to 80% reduction by 2050 for light-duty vehicles. The most significant emission reduction by AVs is the change in the mobility model [31,32] As mentioned above, fuel consumption can be reduced by eco-driving, which is faster and has relatively lower costs than changing the whole fleet to more advanced vehicles [33,34]. Eco-driving showed an improvement in fuel efficiency by up to 45% [35].…”
Section: Autonomous Vehicles(avs)mentioning
confidence: 99%
“…These questions are still in discussion and the answers are uncertain. Driven by the development of technology, the AVs are to be incorporated into MaaS [6,7]. Several applications exist to fulfill the MaaS requirements; however, what are the available functions on the application of MaaS based on AVs?…”
Section: Maas Smartphone Applicationmentioning
confidence: 99%
“…The literature about services of shared autonomous vehicles (SAVs) is summarized in a comprehensive review paper [8], regarding aspects of (1) Traffic and Safety, (2) Travel behavior, (3) Economy, (4) Transport supply, (5) Land use, (6) Environment, (7) Governance. An SAV typology is proposed and concluded that the deployment of AVs may be as shared autonomous mobility services.…”
Section: Maas Smartphone Applicationmentioning
confidence: 99%